2010
DOI: 10.1007/bf03346588
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin protects diabetic rats against kidney injury through the suppression of renal matrix metalloproteinase-9 expression

Abstract: Simvastatin may has a potential therapeutic target in diabetic nephropathy, which may be partly attributed to down-regulating over-expression of MMP-9 in renal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
6
22
0
1
Order By: Relevance
“…These contradictions could be caused by differences in animal strains, samples obtained, and cell types examined, as well as the fact that diabetes treatment affects MMP expression (126). Some models show that decreased MMP activity, particularly of MMP-2 and MMP-9, ameliorate kidney lesions (107,114,144,150), whereas in other models maintenance of MMPs, namely, MMP-1 and in some cases even MMP-9, is associated with improvement (see Table 2) (4,34). Similarly contradictory, TIMP-3 was elevated in diabetes, but TIMP-3 null mice actually had worsened fibrosis and increased activation of MMP-2 (55,57).…”
Section: Mmps In Renal Pathologymentioning
confidence: 99%
“…These contradictions could be caused by differences in animal strains, samples obtained, and cell types examined, as well as the fact that diabetes treatment affects MMP expression (126). Some models show that decreased MMP activity, particularly of MMP-2 and MMP-9, ameliorate kidney lesions (107,114,144,150), whereas in other models maintenance of MMPs, namely, MMP-1 and in some cases even MMP-9, is associated with improvement (see Table 2) (4,34). Similarly contradictory, TIMP-3 was elevated in diabetes, but TIMP-3 null mice actually had worsened fibrosis and increased activation of MMP-2 (55,57).…”
Section: Mmps In Renal Pathologymentioning
confidence: 99%
“…This relationship is described as being either organ-specific or tissue-specific [40][41][42]. We did not evaluate the levels of MMPs in adipose tissue; therefore, we could not explain how a change in fat mass, with a subsequent alteration in local environment, influences circulating blood levels of these proteins.…”
Section: Limitationsmentioning
confidence: 99%
“…Abnormal expression of MMPs is involved in many pathological processes including diabetes (Buraczynska et al, 2015;Liu et al, 2013). In diabetic nephropathy, the change of MMPs expression and activity directly influences the deposition of ECM (Yao et al, 2010). Previous studies have demonstrated that MMPs were upregulated in diabetic nephropathy (Yao et al, 2009) and inhibition of MMPs produced the amelioration of ECM accumulation in the settings of established fibrosis (Lutz et al, 2005;Tashiro et al, 2004).…”
Section: Introductionmentioning
confidence: 97%